Design of an efficient fully nonvolatile and radiation-hardened majority-based magnetic full adder using FinFET/MTJ. (September 2020) - Bakhtavari Mamaghani, Sina; Moaiyeri, Mohammad Hossein; Jaberipur, Ghassem
Abstract: As transistor dimensions reach sub-micron scales, new challenges such as power efficiency and radiation effects that were previously negligible, have become a matter of great concern. One of the promising methods to overcome these challenges is a hybrid design based on magnetic tunnel junctions (MTJ) and FinFETs. In this paper, an efficient fully nonvolatile and radiation-hardened cascadable magnetic full-adder (MFA) is proposed based on majority logic. The design has been optimized to achieve high power efficiency and low area overhead. SPICE simulations are carried out using MTJ compact model and 7 ​nm FinFET technology. A comprehensive comparative analysis is reported regarding power, performance, area, nonvolatility, radiation hardness, and process variations. In conclusion, our MFA design has demonstrated improvements in total power consumption, leakage power, and area up to 71%, 64%, and 72%, respectively, while putting forward high-reliability, full nonvolatility, and radiation hardness. These features, present our design as a feasible candidate for the future high reliable and nonvolatile VLSI circuits.